Games Transmogrified to Make Classroom Teaching More Effective - Duggal, Kavisha; Gupta, Lovi Raj; Kavya Sri, G (International Journal of Computer Sciences and Engineering, 2025)
In this 21st century it is important to reinvent future of students by adopting unseasoned and interesting methods for classroom teaching. In this paper, games which everyone is familiar in day-to-day life are transmogrified and embedded into the classroom teaching to make the learning more ingrained and emphatic. To enhance classroom engagement it is very important to adopt classified teaching strategies which make the neoteric students to attend the classes without attendance compulsion. The games discussed in the paper are not subject or stream dependent, they can be easily modified and implemented with minor change to create a reasonable fun and learning environment. Games are competitive in nature which inbuilt the problem solving skills among the students through various stages of activities involved in game play. Implementation of games in education helps students to achieve planning, strategic thinking, communication skills, group decision making, negotiating skills and the most important gain in knowledge.